Objetivos de desenvolvimento sustentável e saneamento básico: uma análise da política pública de financiamento condicionado para o Programa Minha Casa, Minha Vida - Almeida, Amanda de Oliveira (2019)
The Sustainable Development Goals are the new development agenda of the United Nations, approved in September 2015. It brings the discourse that it will be necessary to go beyond the three pillars — social, environmental and economic —, because development will be achieved only if it incorporates the principles of human rights and good governance. Each country must appropriate the objectives in order to respect the local history and the capacity to achieve them, as it must also recognize the importance of the private sector and its involvement in shaping a more just and environmentally resilient society. Based on the discussion about the theory of justice as equity of John Rawls and the capabilities approach of Amartya Sen and Martha Nussbaum, this research highlights how the sanitary condition affects life quality, as it is also related to other areas such as health, education and work. Thus, the research tried to explore how the modifications on the Minha Casa Minha Vida Program can contribute to the achievement of the "SDG 6 – Clean Water and Sanitation" and, consequently, promote the social-environmental justice. Through the analysis of the Program’s documents, it was acknowledged that the law is similar with the principles of social and environmental justice, establishing improvements in the life quality. Nevertheless, for the private sector of construction the constant modifications in the law do not bring the legal security necessary for investments to provide adequate houses for the most vulnerable population, which continues to suffer with inhuman deprivation. In order to these people have the substantive freedom to choose the way of life they want, a change is needed in the way Brazil designs its public policies on sanitation and habitation, so that there is a larger involvement of the investors, as it can favour the improvement of life quality of the people.